STRATEGI PENGEMBANGAN WIRAUSAHA GULA KELAPA DI PERDESAAN - Sulistyani Budiningsih; Tri Septin Muji Rahayu; Rina Mudjiyanti (Agritech: Jurnal Fakultas Pertanian Universitas Muhammadiyah Purwokerto, 2017)
The purpose of this research is 1) to identify the economic and non economic problems (technical and managerial) which become the constraint of local coconut sugar producer with local wisdom in Kasegeran Village, Cilongok District, 2) To find the strategy of coconut sugar entrepreneurs development in Kasegeran Village, Cilongok DistrictThe research method is conducted by survey which take sample from population and use questioner as data collecting tool (Singarimbun, 2008). Research activities in the form of descriptive research quantitative and qualitative, that aims to find facts with interviewing techniques, observation and documentation . Research location in the Village District Kasegeran Cilongok Banyumas regulated purposively (Purposive Sampling) based on the potential of local resources and the existence of entrepreneur entrepreneurs processed palm into coconut sugar superior products. the sample of research was deliberately determined by 20 sugarcane craftsmen. The formulation of coconut sugar coconut development strategy was analyzed through SWOT analysis (Strengths, Weaknesses, Opportunities, Threats).Results shows that the strategy that needs to be applied in the form of Aggressive Strategy. From the SWOT matric can be known the strategy of coconut sugar entrepreneurs as follows : experience and entrepreneurial spirit of entrepreneur who owned and supported the potential of local resources as a force in realizing coconut sugar production goes continuously. Increased coconut production potential increase tends to increase especially the existence of partnership relationship between coconut business entrepreneur and business opportunity is still wide open and continuous development from government and related institution